Illegal Discharge: Exploring the History of the Criminal Enforcement of the U.S. Clean Water Act - Joshua Ozymy (2021)
The criminal prosecution of defendants that violate federal clean water laws has been ongoing for roughly four decades. Yet, we continue to have a poor understanding of how federal prosecutors use the U.S. Clean Water Act (“CWA”) to charge and prosecute criminals and the outcomes of those prosecutions. We use content analysis to analyze 2,588 federal criminal prosecution case summaries, 1983-2019, to gain a better historical understanding of how the CWA has been used as a prosecutorial tool, to bring out the major themes in the prosecutions, and quantify sentencing outcomes. Findings from the 828 CWA prosecutions undertaken during this time period suggest that charging patterns center on four themes, which fall in line with the EPA’s compliance monitoring strategy for the CWA: illegal discharge, illegal dredging and filling, false reporting, and tampering with a monitoring device. Total punishments include over $1.2 billion in monetary penalties, 34,600 months probation, and 5,269 months incarceration